Towards a relevant framework for establishing the semiology of architecture in Kenya required for architectural dialogue in the creation of a Critical Regionalist Kenyan architecture - Bakker, Karel Anthonie (University of Pretoria, 2014)
Dissertation (MArch(Prof))--University of Pretoria, 2013.